O acervo de obras raras da Biblioteca Central da Universidade Federal do Pará - SOARES, Luciana Nogueira (2019)
Documentary research on the collection of rare works from the Central Library of the Federal University of Pará, dating from the seventeenth century to the twentieth century featuring titles from different areas of knowledge. As an important source of information there is a need for developing an electronic catalog that allows users to delve into the most varied subjects. Consultation know this can be done online, but the Central Library does not yet have a catalog automated search through the bibliography of computerized equipment. The methodological approach drew on a literature survey of the collections available in the library. Highlight some works in every century and demonstrate quantitatively, through graphics, titles available in each period and the topics covered. In this context, concludes the research showing the importance of the electronic catalog as a tool for information retrieval